The Influence of Tourism Facilities and Destination Image on Visiting Decisions at Rio Beach by the Beach, South Lampung - Jundi Naufal Habibi; Maulana Agung P; Prasetya Nugeraha (Cita konsultindo, 2025)
Rio by the Beach Beach in South Lampung has great potential as a leading touristdestination, but competition with other beaches in the surrounding area and lessthan optimal management are obstacles in increasing tourist visits. The researchersset out to find out how factors like physical attractiveness and geographical proximityaffected people's propensity to have sexual relations. This study employed anexplanatory research methodology with a quantitative approach. One hundredguests visiting Rio by the Beach filled out the surveys that were used to gather data.Multiple line regression tests were used to examine the data. The researchersdiscovered that tourist attractions had a positive impact on sales by 21.7% anddestination services by 52.7%. There was a 56.9% influence of both variables ontourists' decision to travel. These findings indicate that adequate tourist facilities anda positive destination image can increase tourist comfort, satisfaction, and trust inchoosing Rio by the Beach Beach as a tourist destination.